Beyond the balance sheet: How green accounting, innovation, and regulation shape sustainable growth in middle-income economies - Zakaria Abubakari; Redruth Nyaaba Ayimpoya; Mohammed Owusu (Social, Ecology, Economy for Sustainable Development Goals Journal, 2026)
Background: This study investigates the influence of green accounting practices on economic growth in middle-income economies, emphasizing the mediating role of technological innovation and the moderating effect of regulatory quality. It seeks to clarify whether environmental accounting frameworks can simultaneously support economic expansion and sustainability across diverse institutional and innovation contexts. Methods: Guided by Ecological Modernization Theory, Endogenous Growth Theory, and Institutional Theory, the study uses balanced panel data from 24 middle-income countries spanning 2010–2023. Fixed-effects regressions assess direct effects, Baron and Kenny’s (1986) mediation framework examines technological innovation’s role, and moderated regression models evaluate regulatory quality’s conditioning influence. Findings: Green accounting significantly enhances aggregate GDP growth but may constrain short-term per capita welfare, reflecting transitional distributional trade-offs. While green accounting promotes technological innovation, this channel does not mediate its effect on economic growth. Strong regulatory quality, particularly rule-of-law enforcement, amplifies the positive impact of green accounting on economic performance. Conclusion: Policymakers should integrate green accounting into broader governance and innovation strategies. Aligning environmental disclosure with fiscal incentives, R&D investment, and transparent regulatory systems can foster inclusive and sustainable growth trajectories. Findings may have limited generalizability across all middle-income economies due to institutional heterogeneity and data constraints. Future studies could expand country coverage and examine sector-specific effects. Novelty/Originality of this article: The study offers an integrated empirical framework demonstrating how institutional quality and innovation capacity jointly shape the developmental returns of green accounting, providing actionable insights for sustainable growth in emerging economies.